2019
DOI: 10.1080/2162402x.2019.1580128
|View full text |Cite
|
Sign up to set email alerts
|

Sub-cutaneous Fat Mass measured on multislice computed tomography of pretreatment PET/CT is a prognostic factor of stage IV non-small cell lung cancer treated by nivolumab

Abstract: Introduction: Our aim was to explore the prognostic value of anthropometric parameters in patients treated with nivolumab for stage IV non-small cell lung cancer (NSCLC). Methods: We retrospectively included 55 patients with NSCLC treated by nivolumab with a pretreatment 18 FDG positron emission tomography coupled with computed tomography (PET/CT). Anthropometric parameters were measured on the CT of PET/CT by in-house software (Anthropometer3D) allowing an automatic multi-slice measurement of Lean Body Mass (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
48
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(54 citation statements)
references
References 35 publications
4
48
2
Order By: Relevance
“…The remaining 26 studies were subsequently reviewed and screened according to our inclusion and exclusion criteria. Finally, 18 studies were included in our systematic review ( Figure 2 ) [ 18 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ]. The included studies were published between 2018 and 2020, and were retrospective studies, either single or multicenter; one study was a pooled analysis of patients treated with immunotherapy in the context of phase 2 and 3 trials.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The remaining 26 studies were subsequently reviewed and screened according to our inclusion and exclusion criteria. Finally, 18 studies were included in our systematic review ( Figure 2 ) [ 18 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ]. The included studies were published between 2018 and 2020, and were retrospective studies, either single or multicenter; one study was a pooled analysis of patients treated with immunotherapy in the context of phase 2 and 3 trials.…”
Section: Resultsmentioning
confidence: 99%
“…It should be noted, however, that the cutoff for overweight category in this study was BMI ≥19.1 kg/m 2 [ 28 ]. Then, two smaller single-center reports found no association of BMI with oncological outcomes, but showed that pre-treatment weight loss (HR 1.19, p = 0.16) [ 27 ] and low subcutaneous fat mass (SCFM) (HR 0.75, p = 0.006) [ 26 ] were predictors for poor survival outcomes in NSCLC patients treated with nivolumab.…”
Section: Resultsmentioning
confidence: 99%
“…The remaining 27 studies were subsequently reviewed and screened according to our inclusion and exclusion criteria. Finally, 13 studies [13][14][15][16][17][23][24][25][26][27][28][29][30] were included in our meta-analysis ( Fig. 1).…”
Section: Characteristics Of Eligible Studiesmentioning
confidence: 99%
“…Moreover, some preclinical data also revealed that obesity increases amount of aged T cell with higher PD-1 expression and dysregulated immune function, which could make cancer cells more sensitive to ICIs therapy [15]. Although several researches have investigated the association between the BMI and ICIs efficacy, heterogeneous conclusions were revealed in these studies [16,17]. Therefore, a high-grade meta-analysis was required to evaluate the relationship between patients BMI and ICIs efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…Another indirect predictive factor is the determination of body composition parameters on the anatomical CT associated with the PET. Therefore, in a study including 55 patients with NSCLC treated by nivolumab, whole-body subcutaneous fat mass measured automatically on the CT of the PET was a significant prognostic factor with a better prognosis for fatty patients (HR = 0.75, p = 0.006 in multivariate analysis) [27,28], possibly because adipocytes in the human obese subcutaneous fat mass release several pro-inflammatory cytokines and chemokines, which contribute to the establishment and maintenance of local and systemic inflammation [29].…”
Section: F-fdg Pet/ctmentioning
confidence: 99%